The "Freight Allowed" Method of Price Quotation - Mund, Vernon A. (Quarterly Journal of Economics, 1940)
Development of the policy, 232.— Freight allowed to destination, 233.— Freight allowed and prepaid, 234.— Freight allowed within zones, 235.— Freight allowed to distributing points, 236.— Characteristics of goods sold freight allowed, 237.— Reasons given by sellers, 237.— Real reason for the policy, 240.— Discrimination involved in the policy, 242.— The open f.o.b. factory policy, 243.— Summary, 245.